Urban Forests as Green Infrastructure: Linking Vegetation Composition, Spatial Distribution, and Environmental Functions - Riska Amanda; Joumaa Abdulwahab; Dang Thi Thanh Tam (Journal of Academic Biology and Biology Education, 2026)
Purpose of the study: This study aimed to analyze the species composition, vegetation structure, spatial distribution patterns, and ecological functions of urban forest vegetation in supporting environmental quality improvement and sustainable urban development. Methodology: A field survey using a complete census approach was conducted to inventory all tree and pole vegetation. Data collection included species identification, diameter measurement, and GPS coordinate recording. Vegetation structure was analyzed using density, dominance, and Importance Value Index, while spatial distribution patterns were mapped using GIS and ArcGIS 10.1. Ecological functions were evaluated based on carbon sequestration and air pollution mitigation capacities of dominant species. Main Findings: The study recorded 35 vegetation species with 1,389 individuals, consisting of 1,250 trees and 139 poles. Swietenia macrophylla was identified as the dominant species with the highest density and IVI values. Spatial analysis revealed a heterogeneous distribution pattern with high-density clusters dominated by Swietenia macrophylla and Terminalia catappa. Dominant species significantly contributed to ecosystem services, including carbon sequestration, pollution reduction, microclimate regulation, and ecosystem stability. Samanea saman, Swietenia macrophylla, and Pometia pinnata were identified as key species supporting environmental quality improvement. Novelty/Originality of this study: This study integrates vegetation inventory, stand structure analysis, ecological importance assessment, and GIS-based spatial distribution mapping within a single framework, providing comprehensive scientific evidence to support sustainable urban forest management, biodiversity conservation, and environmental planning.